Einbruchhemmung mit Mauerwerk aus Leichtbeton. Issue 1 (11th February 2020) - Frank, Alexander; Heinrichsberger, Sandra; Kranzler, Thomas; Küenzlen, Jürgen H. R.; Sack, Norbert
Abstract: Die Produktpalette von Mauersteinen aus Leichtbeton weist sowohl schwere, hochfeste Steine für Innenwände, Haustrennwände sowie zweischalige und zusatzgedämmte (WDVS) Außenwände als auch leichte, hochwärmedämmende Steine für monolithische Außenwände auf. Während die Montage einbruchhemmender Bauelemente in Mauerwerk aus schweren, hochfesten Steinen aus Leichtbeton seit jeher in DIN EN 1627 bis hin zur Widerstandsklasse RC 6 geregelt ist, war die Montage in leichten, hochwärmedämmenden Steinen für monolithische Außenwände aus Leichtbeton bislang nicht abgedeckt. Aus diesem Grund wurden durch das ift Rosenheim Untersuchungen zur Einbruchhemmung von hochwärmedämmendem monolithischem Leichtbetonmauerwerk durchgeführt. Für übliches, 365 mm dickes und mit einem Leichtputz Typ I verputztes Leichtbetonmauerwerk der Steindruckfestigkeitsklasse 2 und der Rohdichteklasse 0, 40 wurde die in Deutschland von der Polizei empfohlene Einbruchwiderstandsklasse RC 2 nachgewiesen. Die Ergebnisse des Forschungsprojekts mündeten in einem Vorschlag für die Ergänzung der Tabelle NA.2 des deutschen Nationalen Anhangs zu DIN EN 1627. Abstract: Burglary resistance with lightweight concrete masonry The product palette of lightweight concrete blocks ranges from heavy, high‐strength blocks for internal walls, cavity walls and externally insulated (ETICS) external walls to lightweight, highly insulating blocks with lower density and lower compressive strength for monolithic external walls. In the German National Annex to EN 1627, suitable wall constructions for the installation of burglary‐retarding building elements are given. Masonry walls made of heavy, high‐strength blocks fulfil all requirements up to the highest resistance class RC 6. The installation of burglary‐retarding building elements in modern, highly insulating blocks for monolithic masonry is therefore not covered by the standard yet. At the institute for window technology in Rosenheim ( ift Rosenheim ), testing has been undertaken of the burglary resistance of building elements installed in monolithic masonry made of highly insulating lightweight concrete blocks. For the usual 365 mm thick lightweight concrete masonry units of compressive strength class 2 and density class 0.40 with a lightweight plaster of Type I, the burglary resistance class RC 2 (recommended by the police in Germany) was verified in all the investigated variants of blocks. The results of the research project have been implemented in a proposed change of the German National annex to DIN EN 1627.